Terbentuknya Provinsi Banten Dinamika Pemerintahan di Banten, Terbentuknya Dinasti Politik, Hegomoni Selama Reformasi Hingga Kekinian (International Forum of Researchers and Lecturers, 2025)
This study aims to understand and analyze the long journey of Banten Province, from its formation process to the political and governmental developments that have taken place within it. We used a historical-analytical qualitative approach with the aim of providing an in-depth analysis of the long journey of Banten Province. The issues studied range from the formation process of Banten to the political and governmental developments that have taken place within it. The results of our research show that the formation of Banten Province as part of decentralization and regional autonomy has not been entirely successful in eliminating the dominance of political dynasties. This practice limits the space for community participation and strengthens political oligarchy, so efforts need to be made to increase and provide community participation in the political dynamics in Banten and strengthen local democracy. This study suggests that efforts are needed to increase community participation, strengthen local democracy, and overcome political dynasties in order to improve the welfare of the people of Banten.